Developing a~smart energy service canvas - Jennifer Günter; Lukas Fabri; Simon Wenninger; Can Kaymakci (Schmalenbach Journal of Business Research (SBUR), 2025)
Rising energy and CO2 prices are driving industrial companies to focus increasingly on energy efficiency and flexibility to remain competitive. Besides technical improvements, smart energy services like nonintrusive load monitoring (NILM) are promising approaches to increasing a~company's energy efficiency and flexibility potential. Despite its advantages, smart energy services are not yet widely used in practice, and service providers are cautious. Existing research investigates almost exclusively technical aspects of smart energy service applications and systems, particularly for NILM, while a~business model perspective is missing. This study addresses this research gap following a~design science research approach with literature research and expert interviews, and develops a~business model framework-the Smart Energy Service Canvas (SESC). The SESC is a~practical and empirically validated tool to formalize, structure, and implement a~business idea on smart energy services.
Keywords: 650; Business model; Data-driven services; Nonintrusive load monitoring; Smart energy services; Smart manufacturing; Sustainable manufacturing